CHARACTER BELIEF AND BEHAVIOUR POTRAYED IN M.NIGHT SHYMALAN’S DEVIL (2010) AS A PSYCHOANALYSIS STUDY - Destha Pratama Putra; Endang Yuliani Rahayu (Universitas Stikubank (UNISBANK) Semarang, 2020)
This research entitled Character Belief and Behaviour Potrayed in M. Night Shyamalan’s Devil (2010) As A Psychoanalysis Study. In this research the researcher analyzes the character belief and behaviour toward superstition in M. Night Shyamalan’s Devil (2010). The object used in this research is a film by M. Night Shyamalan entitled Devil In analyzing the data researcher applied a qualitative research. The technique that used to analyze the film is by reading the script and watching the movie and then the researcher applied Carl Gustav Jung's theory of consciousness, namely personal unconscious, collective unconscious, and archetype. Data is collected by watching films and reading dialogue scripts. After analyzing the data it can be concluded that the reason why the character believes in superstition is due to the story of the character's mother and opinions that are repeated over and over. The behavior that is reflected by the character after believing in superstition is the character trying to solve the case using a religious point of view. Meanwhile the effect that arises after believing in superstition is that they succeed in knowing and realizing that the mastermind behind the case is devil.